Representasi Perseptual Mapping Masyarakat Terhadap Perbedaan Kualitas Transportasi Di Surabaya Dengan Multidimensional Scalling - Syaugi Sungkar, Salman; Khairian, Farhan Aldan; Marpaung, Josua Ronaldo Davico; Hardiansyah, Fernanda Rizky; Saifudin, Toha; Ana, Elly (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
Infrastructure is one of the important factors in driving economic growth, and transportation is an inseparable part of it. This research aims to assess the sustainability of transportation in Surabaya City by looking at the level of user satisfaction from four main aspects, namely speed, comfort, safety, and price. The research was conducted in 2025 by involving 32 respondents. The data was analyzed using the Multidimensional Scaling (MDS) method, which was used to map six types of transportation modes: Indonesian Railways (KAI) Local, Suroboyo Bus, motorcycle online ojek, car online ojek, TransJatim Bus, and city transportation (angkot) or wara-wiri. The results show that Suroboyo Bus obtained the highest satisfaction score from users, with an average value of 3.13. Meanwhile that, the results of MDS mapping divide transportation modes into four groups, namely The first quadrant contains KAI Local and city transportation, the second quadrant is only filled by online motorcycle taxis, the third quadrant is inhabited by online car taxis, the fourth quadrant includes two bus-based transportation modes, namely Suroboyo Bus and TransJatim Bus. This model is evaluated using stress value of 0.06650 and RLQ of 0.97611. Both values indicate that the model is classified as good and reliable to describe customer satisfaction perceptions of transportation modes in Surabaya.